The Impacts of the COVID-19 Pandemic on Service-Learning Experiences Among Undergraduate Public Health Students in Hawai‘i - Kehl, Lisa; Patil, Uday; Tagorda, Michelle; Nelson-Hurwitz, Denise C. (Frontiers in Public Health, 2022)
Service-learning is a high-impact educational practice at the core of the undergraduate public health degree at the University of Hawaiʻi at Mānoa (UHM). This practice provides an invaluable learning experience and professional opportunity for students to collaborate with community partners and make significant contributions in the field. The COVID-19 pandemic halted or disrupted service-learning experiences as community partners adapted to shifting mandates and emergency orders. Surveying the rapidly evolving landscape of partner organizations to support service learning is a challenge. Assessing changes to the program mentorship or satisfaction is the first step to developing protocols to ensure standardization of service learning during times of crisis. This study will address if and how the pandemic impacted students’ satisfaction with required service learning experiences. Furthermore, authors hope to create a comprehensive list of practicum partnering organizations, both focused on pandemic response and, more generally, of the service-learning students at UHM, with the intent to increase students and community partners in local service learning. Assessments were conducted to assess the impact of COVID-19 on undergraduate students’ experiences with service learning through use of a program exit survey. The authors hypothesized pandemic-related adjustments would not affect student satisfaction or skill development. Despite challenges associated with the pandemic and emergency online transitions, students persisted in personal and professional growth associated with service learning. This developed resilience supports students as they graduate and enter a workforce adapting to remote work demands and community needs.